Design and Performance of Amorphous Silicon Based on Uncooled Bolometer-Type Infrared Focal Plane Arrays - Van Trieu Tran; V. R. Stempitsky; I. Yu. Lovshenko; K. V. Korsak; Dinh Ha Dao (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Uncooled bolometric type thermal detectors, combined into a matrix and placed into a focal plane array have the following characteristics: low cost, operation at room temperature, compatibility with the silicon CMOS technology, and high detecting performance; therefore recently it became a hot spot in infrared or terahertz detection field. The performance of uncooled infrared focal plane detector arrays depends on the optimization of critical parameters which are determined by geometrical design and the electrical, optical, and thermal physical properties of the detector materials. We report the study of a fabrication process and characterization of two (2D) dimensional arrays of uncooled microbolometers based on silicon (α-Si) thermo-sensing films. Because these arrays substantially reduce sensor size, they are becoming the preferred format for most modern applications.